The Health Effect of the Number of Children on Chinese Elders: An Analysis Based on Hukou Category - Long, Cuihong; Han, Jiajun; Yi, Chengzhi (Frontiers in Public Health, 2021)
Based on 2018 China Health and Retirement Longitudinal Study (CHARLS 2018), from the perspective of urban-rural disparity, this paper investigates how fertility affects Chinese elders’ health. We exploit the enactment of one-child policy in 1979 to construct instrumental variables capturing the health effect of having only one child rather than multiple children. The empirical results show that the health condition of elders having only one child is worse than elders having multiple children. Moreover, the negative health effect of having only one child is more prominent for rural elders. After considering the selection on both levels and gains, the results are still robust in Marginal Treatment Effect (MTE) estimation. The mechanism analysis suggests that having only one child instead of multiple children depressed the upstream intergenerational transfer payments, and the received transfer payments of rural parents have been pared more by only having one child, therefore, lower fertility puts more down pressure on rural elders’ health status. Our findings have important implications, in the context of increasing population aging, the urban-rural inequality caused by the hukou system have been magnified by the declining fertility rate. Chinese government should pay more attention to rural elders with only one child, and more public funded socioeconomic resources are needed for one-child parents in rural areas to improving their health.